1983
DOI: 10.1017/s0033291700051047
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of community psychiatric nurse or out-patient psychiatrist care of neurotic patients

Abstract: SYNOPSISIn a prospective controlled investigation chronic patients, the majority with neurotic conditions, were randomly allocated either to community psychiatric nurses (CPN) as the main therapist or to routine out-patient psychiatrist follow-up. There was no statistically significant difference in the mean public expenditure for the two modes of care. The direct costs of psychiatric care comprised a small proportion of total public expenditure and were initially greater in the nursing group. Subsequently, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Especially in mental health care, psychosocial costs such as grief and loss of well-being play a major role. Seven studies 1,68,72,78,118,130,145 mentioned these costs as being relevant and tried to fit them into the analysis.…”
Section: Assessing Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in mental health care, psychosocial costs such as grief and loss of well-being play a major role. Seven studies 1,68,72,78,118,130,145 mentioned these costs as being relevant and tried to fit them into the analysis.…”
Section: Assessing Costsmentioning
confidence: 99%
“…One can use records available through health service suppliers. 3,56,57,68,69,76,79,102,108,110,116,121,122,127,130,[144][145][146][147] In addition, caseregisters or other macro-level records (e.g. Medicaid records, California County Public Mental Health Information System) can be employed to glean information from several institutions.…”
Section: Measurement Of Costsmentioning
confidence: 99%
“…In the field of mental health, there have been numerous economic comparisons of treatment by specialist mental health professionals with the care given by GPs or other types of specialists (Gunderson & Mosher, 1975;Weisbrod et al 1980;Fenton et al 1982;McKechnie et al 1982;Mangen et al 1983;Ginsberg et al 1984;Balestrieri et al 1988). Each presents a distinct choice which is of relevance to health service policy-makers.…”
Section: Economic Analysismentioning
confidence: 99%
“…Community psychiatric nurses, in a randomized controlled trial, were shown to bring greater clinical and economic benefits than routine psychiatric outpatient follow-up in the management of adults Family therapy in the home 191 with neurotic disorders (Paykel et al, 1982;Mangen et al, 1983). The patients in this study also showed greater satisfaction with the nursing mode of follow-up and were particularly positive about the fact that the nurses made home visits .…”
mentioning
confidence: 71%